1993
DOI: 10.1007/bf01321832
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of bone turnover in elderly women with hip fracture

Abstract: Hip fracture is one of the most severe consequences of osteoporosis affecting aged women. However, abnormalities of bone turnover responsible for bone loss in this condition have not been clearly defined. To further evaluate the bone metabolic status of women sustaining hip fracture, we have prospectively measured serum osteocalcin as a marker of bone formation and urinary excretion of pyridinoline (Pyr) and deoxypyridinoline (D-pyr) cross-links as markers of bone collagen degradation in 174 independently livi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
32
0
2

Year Published

1993
1993
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(41 citation statements)
references
References 44 publications
7
32
0
2
Order By: Relevance
“…It is now widely accepted that the accelerated rate of bone loss seen after the menopause is mainly due to an uncoupling in bone turnover and an increase in bone resorption (26,27). Studies employing specific bone markers indicate that bone turnover continues to be increased (and to be associated with bone loss) during late menopause (28)(29)(30)(31)(32)(33). In some postmenopausal women (34), but particularly in the very elderly (35)(36)(37), this increase in bone turnover is often, but not always, found to be due to vitamin D and/or calcium deficiency and secondary hyperparathyroidism.…”
Section: Menopause and Ageingmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now widely accepted that the accelerated rate of bone loss seen after the menopause is mainly due to an uncoupling in bone turnover and an increase in bone resorption (26,27). Studies employing specific bone markers indicate that bone turnover continues to be increased (and to be associated with bone loss) during late menopause (28)(29)(30)(31)(32)(33). In some postmenopausal women (34), but particularly in the very elderly (35)(36)(37), this increase in bone turnover is often, but not always, found to be due to vitamin D and/or calcium deficiency and secondary hyperparathyroidism.…”
Section: Menopause and Ageingmentioning
confidence: 99%
“…In retrospective population-based studies, Akesson and co-workers (28,29,43,44) have demonstrated that previous fractures were associated with abnormal bone turnover. After adjustment for age and BMD, women with fractures occurring within six years prior to the study were characterised by lower serum levels of OC and PICP, but normal rates of bone resorption.…”
Section: Bone Turnover In Osteoporosismentioning
confidence: 99%
“…On the other hand, using more sensitive biochemical markers, the osteocalcin level was 20 percent lower in women with hip fracture, whereas the bone resorption, as measured by the pyridinoline excretion, was 40 percent higher. Thus, elderly women with hip fracture presented biochemical evidence of an imbalance of bone turnover with decreased formation and increased resorption, a bone metabolic deficiency which may play a role in the development of a low bone mass (134). However, the ability to increase the bone turnover in response to the fracture-healing process was intact; osteocalcin and ALP were increased at 3-7.5 months after the fracture (133).…”
Section: Fracturementioning
confidence: 99%
“…Bone mineral density (BMD) is widely used to estimate bone fracture risk. In addition, evaluation of bone turnover rate is established as an independent predictor for bone fracture (2,3 ) and future bone loss (4 ), and measurements of bone metabolic markers are increasingly used to complement BMD measurements (5,6 ). Bone resorption markers are assumed to be superior to bone formation markers for predicting future changes in bone mass, well in advance of detection of BMD reductions (7 ).…”
mentioning
confidence: 99%